2015
DOI: 10.4103/0300-1652.153406
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coconut oil in plaque related gingivitis - A preliminary report

Abstract: Background:Oil pulling or oil swishing therapy is a traditional procedure in which the practitioners rinse or swish oil in their mouth. It is supposed to cure oral and systemic diseases but the evidence is minimal. Oil pulling with sesame oil and sunflower oil was found to reduce plaque related gingivitis. Coconut oil is an easily available edible oil. It is unique because it contains predominantly medium chain fatty acids of which 45-50 percent is lauric acid. Lauric acid has proven anti inflammatory and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
96
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(109 citation statements)
references
References 19 publications
8
96
0
5
Order By: Relevance
“…and Prevotella spp. The decline in bacterial viability after the administration of VCO is due to its antibacterial content, namely, the lauric acid that kills a wide variety of microorganisms whose cell membranes contain lipid acids, such as Gram-positive and Gramnegative bacteria [15,17]. Lauric acid is a nonpolar, saturated lipid acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Prevotella spp. The decline in bacterial viability after the administration of VCO is due to its antibacterial content, namely, the lauric acid that kills a wide variety of microorganisms whose cell membranes contain lipid acids, such as Gram-positive and Gramnegative bacteria [15,17]. Lauric acid is a nonpolar, saturated lipid acid.…”
Section: Discussionmentioning
confidence: 99%
“…Lauric acid is a natural antibacterial agent that can kill microorganisms whose cell membranes contain lipid acids [13,17]. The VCO used in the study was in the following concentrations: 100%, 50%, 25%, and 12.5%.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted [18], VCO used in oil pulling had reduced 22.79% colony growth of Streptococcus mutans (S. mutans) while chlorohexidine showed 25.72% reduction of colonial growth. Among few studies conducted on coconut oil, sunflower oil, sesame oil, and other edible oils against chlorhexidine, results showed that oil pulling is able to reduce halitosis and reduce the bacteria count which causes it to drop to a significant amount, reducing gingivitis and plaque as effectively as chlorhexidine [18][19][20][21]. Furthermore, oil pulling has advantages over chlorhexidine that oil pulling does not leaves staining, no lingering aftertaste, and most importantly no allergy [19].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, oil pulling has advantages over chlorhexidine that oil pulling does not leaves staining, no lingering aftertaste, and most importantly no allergy [19]. Although coconut oil exhibited a significant reduction in S. mutans count after oil pulling [18,21], the coconut oil needs to be pre-digested before consumption to make it more effective [19]. Against oral microflora, oil pulling is found to be effective due to the abundant presence of MCFA in coconut oil and VCO.…”
Section: Introductionmentioning
confidence: 99%
“…Lauric acid, the main component of VCO, has antibacterial, antivirus, and antiprotozoal effects. Lauric acid can kill gram-positive bacteria by damaging the bacterial cell membrane, resulting in membrane lysis and inhibited bacterial growth [9,10].…”
Section: Introductionmentioning
confidence: 99%